Diffuse right ventricular fibrosis in heart failure with preserved ejection fraction and pulmonary hypertension. (5th January 2020) - Patel, Ravi B.; Li, Emily; Benefield, Brandon C.; Swat, Stanley A.; Polsinelli, Vincenzo B.; Carr, James C.; Shah, Sanjiv J.; Markl, Michael; Collins, Jeremy D.; Freed, Benjamin H.
Abstract: Aims: While right ventricular (RV) dysfunction is associated with worse prognosis in co‐morbid pulmonary hypertension and heart failure with preserved ejection fraction (PH‐HFpEF), the mechanisms driving RV dysfunction are unclear. We evaluated the extent and clinical correlates of diffuse RV myocardial fibrosis in PH‐HFpEF, as measured by cardiovascular magnetic resonance‐derived extracellular volume (ECV). Methods and results: We prospectively enrolled participants with PH‐HFpEF ( n = 14), pulmonary arterial hypertension (PAH; n = 13), and controls ( n = 8). All participants underwent high‐resolution cardiovascular magnetic resonance, and case subjects (PH‐HFpEF and PAH) additionally underwent right heart catheterization. T1 mapping was performed using high‐resolution modified look‐locker inversion recovery with a 1 × 1 mm 2 in‐plane resolution. RV free wall T1 values were quantified, and ECV was calculated. Participants with PH‐HFpEF were older and carried higher rates of hypertension and obstructive sleep apnoea than those with PAH. While RV ECV was similar between PH‐HFpEF and PAH (33.1 ± 8.0 vs. 34.0 ± 4.5%; P = 0.57), total pulmonary resistance was lower in PH‐HFpEF compared with PAH [PH‐HFpEF: 5.68 WU (4.70, 7.66 WU) vs. PAH: 8.59 WU (8.14, 12.57 WU); P = 0.01]. RV ECV in PH‐HFpEF was associated with worse indices of RV structure (RV end‐diastolic volume: r = 0.67, P = 0.01) and RV function (RV free wall strain: r = 0.59, P = 0.03) but was not associated with RV afterload (total pulmonary resistance: r = 0.08, P = 0.79). Conversely, there was a strong correlation between RV ECV and RV afterload in PAH ( r = 0.57, P = 0.04). Conclusions: Diffuse RV fibrosis, as measured by ECV, is present in PH‐HFpEF and is associated with adverse RV structural and functional remodelling but not degree of pulmonary vasculopathy. In PH‐HFpEF, diffuse RV fibrosis may occur out of proportion to the degree of RV afterload.